Effect Of Storage Time In Different Humidity Conditions On Mechanical And Physical Properties Of Hybrid Medium Density Fibreboard (MDF) - Yusof, Nur Firdaus Mohamed (2010)
In this research, hybrid medium density fibreboard and medium density fibreboard (MDF) were produced by using rubberwood (RW) and empty fruit bunch (EFB) based on oven dried weight. RW fibres were obtained from Merbok MDF Sdn Bhd in Kedah. While, EFB fibres used to produce those board were obtained from Malaysian Palm Oil board (MPOB) in Bangi. Commercial 12mm thick hybrid medium density fibreboard and medium density fibreboard (MDF) were produced using thermomechanical pulp fibre. The average density of these boards were 650 kg/cm. The resin used was commercial urea formaldehyde with 12% resin content. Those MDF were prepared by dry process. There are 4 different ratio of MDF from rubberwood and EFB used that are EFB: RW, 20: 80, EFB: RW, 50: 50, EFB: RW, 100:0, EFB: RW, 0:100. Three different relative humidity (RH) at 65% RH, 93% RH with fixed temperature at 20C and normal condition (Average temperature, 23˚C-30˚C; RH, 64%-80%) were used to store the boards.